Intracellular Localization of an Osmocenyl‐Tamoxifen Derivative in Breast Cancer Cells Revealed by Synchrotron Radiation X‐ray Fluorescence Nanoimaging. (6th February 2019) - Fus, Florin; Yang, Yang; Lee, Hui Zhi Shirley; Top, Siden; Carriere, Marie; Bouron, Alexandre; Pacureanu, Alexandra; da Silva, Julio Cesar; Salmain, Michèle; Vessières, Anne; Cloetens, Peter; Jaouen, Gérard; et al.
Abstract: A series of tamoxifen‐like metallocifens of the group‐8 metals (Fe, Ru, and Os) has strong antiproliferative activity on the triple‐negative breast cancer cells (MDA‐MB‐231). To shed light on the mechanism of action of these molecules, synchrotron radiation X‐ray fluorescence nanoimaging studies were performed on cells exposed to osmocenyl‐tamoxifen (Oc‐OH‐Tam) to disclose its intracellular distribution. High‐resolution mapping of the lipophilic Oc‐OH‐Tam in cells revealed its preferential accumulation in the endomembrane system. This is consistent with the ability of the amino nitrogen chain of the compounds to be protonated at physiological pH and responsible for electrostatic interactions between Oc‐OH‐Tam and membranes. A comprehensive scenario is proposed that provides new insight into the cellular behavior and activation of Oc‐OH‐Tam and advances the understanding of its mechanism of action. Abstract : Die Elementkartierung eines Osmiumkomplexes mit Antikrebswirkung in menschlichen Krebszellen bei pharmakologisch relevanten Konzentrationen unter Verwendung einer Synchrotron‐Röntgen‐Nanosonde offenbart eine intrazelluläre Verteilung, die das Endomembransystem umfasst.